2018
DOI: 10.1021/acschemneuro.8b00625
|View full text |Cite|
|
Sign up to set email alerts
|

Striatal, Hippocampal, and Cortical Networks Are Differentially Responsive to the M4- and M1-Muscarinic Acetylcholine Receptor Mediated Effects of Xanomeline

Abstract: Preclinical and clinical data suggest that muscarinic acetyl­choline receptor activation may be therapeutically beneficial for the treatment of schizophrenia and Alzheimer’s diseases. This is best exemplified by clinical observations with xanomeline, the efficacy of which is thought to be mediated through co-activation of the M1 and M4 muscarinic acetyl­choline receptors (mAChRs). Here we examined the impact of treatment with xanomeline and compared it to the actions of selective M1 and M4 mAChR activators on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…In primates, muscarinic ACh subreceptors relevant for attention and memory functions ( 12 , 13 , 14 , 15 ) have enhanced densities in the prefrontal cortex (PFC) ( 16 ), suggesting that the PFC may be more sensitive to modulation by AChE inhibitors than posterior brain areas. Moreover, a comparison of transcription factor (CREB [cAMP-response element binding protein]) activation of the PFC and the striatum to muscarinic modulation by xanomeline has reported a 10-fold higher receptor sensitivity of the striatum ( 17 ), consistent with other studies reporting significantly higher muscarinic binding potential and higher AChE activity in the striatum than in other cortical regions ( 18 ). It is unclear how these differences affect ACh modulation of attention functions that depend on the PFC ( 19 ) and of flexible learning functions that are dependent on the striatum ( 20 , 21 ).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In primates, muscarinic ACh subreceptors relevant for attention and memory functions ( 12 , 13 , 14 , 15 ) have enhanced densities in the prefrontal cortex (PFC) ( 16 ), suggesting that the PFC may be more sensitive to modulation by AChE inhibitors than posterior brain areas. Moreover, a comparison of transcription factor (CREB [cAMP-response element binding protein]) activation of the PFC and the striatum to muscarinic modulation by xanomeline has reported a 10-fold higher receptor sensitivity of the striatum ( 17 ), consistent with other studies reporting significantly higher muscarinic binding potential and higher AChE activity in the striatum than in other cortical regions ( 18 ). It is unclear how these differences affect ACh modulation of attention functions that depend on the PFC ( 19 ) and of flexible learning functions that are dependent on the striatum ( 20 , 21 ).…”
supporting
confidence: 83%
“…Rather, the different best doses for VS and flexible learning performance will likely be due to brain area–specific pharmacokinetic profiles of receptor densities, drug clearance profiles, or autoreceptor mechanisms that intrinsically downregulate local drug actions ( 74 , 75 , 76 ). One prediction from the specific distribution and kinetics of nicotinic or muscarinic receptors in the PFC and striatum is that donepezil might, at lower doses, act predominantly in the striatum via activation of muscarinic subreceptors because they have a particularly high binding potential ( 18 ) and respond stronger to muscarinic ACh receptor activation compared with the PFC ( 17 ) (see Supplemental Discussion ). However, it is also possible that donepezil recruits nicotinic receptors, which are upregulated with chronic donepezil use ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinesterase inhibitors remain the main current drug strategy for treating AD symptoms 98 . The NAc has served as a target for therapeutic interventions in AD using muscarinic agonists 22,99 , which have shown some promise in clinical trials, as well as nicotinic receptor agonists that were shown to modify various activities in the NAc. However, ChEIs may cause serious side effects, especially in females 11,21 ; including exacerbated anticholinergic burden 20 and indicating the need to develop more finely tuned ChEI treatments.…”
Section: Discussionmentioning
confidence: 99%
“…T he muscarinic acetylcholine receptors (mAChRs) M1− M5 are a family of five class 1 G protein-coupled receptors (GPCRs), with M1 and M4 predominantly expressed in the brain. 1 They have emerged as important drug targets for a number of neurological disorders, including Alzheimer's disease (AD), Parkinson's disease (PD), and schizophrenia, given the promising procognitive and antipsychotic efficacy demonstrated by xanomeline, an M1/M4preferring mAChR agonist, 2 in two phase II clinical trials. 3,4 However, further clinical development of xanomeline was halted due to significant cholinergic adverse events (AEs).…”
mentioning
confidence: 99%
“…The muscarinic acetylcholine receptors (mAChRs) M1–M5 are a family of five class 1 G protein-coupled receptors (GPCRs), with M1 and M4 predominantly expressed in the brain . They have emerged as important drug targets for a number of neurological disorders, including Alzheimer’s disease (AD), Parkinson’s disease (PD), and schizophrenia, given the promising procognitive and antipsychotic efficacy demonstrated by xanomeline, an M1/M4-preferring mAChR agonist, in two phase II clinical trials. , However, further clinical development of xanomeline was halted due to significant cholinergic adverse events (AEs). It was hypothesized that selective activation of M4, a mAChR subtype primarily expressed in brain, could retain the cognitive and antipsychotic benefits of xanomeline while minimizing cholinergic AEs. , Given that, several M4 subtype-selective mAChR positive allosteric modulators (PAMs) such as LY2033298 and VU0152100 , have been identified.…”
mentioning
confidence: 99%